Pengaruh Tekanan Pekerjaan dan Stres Pekerjaan terhadap Evaluasi Kinerja - Logahan, Jerry M. (Journal the Winners: Economics, Business, Management, and Information System Journal, 2009)
The lawyer profession at this time has become the public spotlight due to their role in upholding justice and defending the oppressed. This noble work requires reliable performance. Therefore, performance evaluation of lawyers needs to be considered. Factors that affect the performance evaluation of lawyers should also be investigated further. The purpose of this study is to see the correlation of job stress and pressure of work on performance evaluation of the lawyers, especially in corporate law firm "H H. Harris Sarana and Partner Law Firm". This research has shown that the effects of job stress and job stress have a significant impact on performance evaluation. Work pressure variable can affect performance evaluation significantly. With the situation now, corporate leaders need to consider the pressures of work and working atmosphere, so performance can be increased. In addition, companies need to improve communications systems and trying to minimize all forms of work stressors, so the lawyers can provide more optimal results in doing their job.